LAW ENFORCEMENT AGAINST THE CRIME OF BURNING PEAT LANDS IN RIAU PROVINCE - Mohd. Yusuf DM; M. Fadli Daeng Yusuf; Siti Yulia Makkininnawa YD; Zulkarnaini Zulkarnaini; Mimin Sundari Nasution (Universitas Syiah Kuala, 2022)
This article discusses aspects of law enforcement related to the criminal act of burning peatlands in Riau Province. The main focus is on law enforcement efforts carried out against environmental crimes, especially those related to peatland burning. Using the case of peatland burning in Riau Province as an example, this article presents an overview of the challenges and steps that can be taken in law enforcement against this serious environmental crime. The discussion involved the role of law enforcement agencies, existing regulations, obstacles in the law enforcement process, as well as strategies to increase prosecution for these violations. The research results show that law enforcement on the criminal act of burning peatlands is necessary to reduce the occurrence of peatland fires caused by human actions. Law enforcement regarding this issue is the main concern, with various aspects such as the role of law enforcement officers, cross-sectoral cooperation, and obstacles experienced in the law enforcement process being the main focus of discussion. Law enforcement against criminal acts of land burning in Riau does not seem to be running optimally.